2018
DOI: 10.1001/jama.2018.18315
|View full text |Cite
|
Sign up to set email alerts
|

Association of Delivery Mode With Pelvic Floor Disorders After Childbirth

Abstract: IMPORTANCE Pelvic floor disorders (eg, urinary incontinence), which affect approximately 25% of women in the United States, are associated with childbirth. However, little is known about the course and progression of pelvic floor disorders over time. OBJECTIVE To describe the incidence of pelvic floor disorders after childbirth and identify maternal and obstetrical characteristics associated with patterns of incidence 1 to 2 decades after delivery. DESIGN, SETTING, AND PARTICIPANTS Women were recruited from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
163
3
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(191 citation statements)
references
References 30 publications
(45 reference statements)
14
163
3
11
Order By: Relevance
“…For each PFD, all study participants contributed data in estimating incidence so that those who developed the PFD prior to study entry contributed to the analysis as leftcensored observations; those who developed the PFD during follow-up contributed as uncensored observations; and those who exited the study free of the disorder contributed to the analysis as right-censored observations. 16 Conventional lognormal models were used to estimate the cumulative incidence of each PFD from first delivery over time, stratified by pelvic floor muscle strength (ie, <20 cm H 2 O or 20 cm H 2 O). As delivery mode is associated with both PFDs 16 and pelvic muscle strength, 12 we further stratified based on delivery mode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each PFD, all study participants contributed data in estimating incidence so that those who developed the PFD prior to study entry contributed to the analysis as leftcensored observations; those who developed the PFD during follow-up contributed as uncensored observations; and those who exited the study free of the disorder contributed to the analysis as right-censored observations. 16 Conventional lognormal models were used to estimate the cumulative incidence of each PFD from first delivery over time, stratified by pelvic floor muscle strength (ie, <20 cm H 2 O or 20 cm H 2 O). As delivery mode is associated with both PFDs 16 and pelvic muscle strength, 12 we further stratified based on delivery mode.…”
Section: Discussionmentioning
confidence: 99%
“…16 Conventional lognormal models were used to estimate the cumulative incidence of each PFD from first delivery over time, stratified by pelvic floor muscle strength (ie, <20 cm H 2 O or 20 cm H 2 O). As delivery mode is associated with both PFDs 16 and pelvic muscle strength, 12 we further stratified based on delivery mode. These models produced time ratios, measuring the magnitude by which times to events expand or contract relative to the reference group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that age at presentation and at onset of UI symptoms was significantly different in the different study groups, whereas the onset of menopause and spontaneous deliveries did not have any influence on the UI type. For spontaneous vaginal delivery, the 15-year cumulative incidence of pelvic floor disorders after first delivery have been described as 34.3% for SUI (11). Other authors described that vaginal delivery is associated with an almost two-fold increase in the risk of long-term SUI and increased risk of UUI (12).…”
Section: Discussionmentioning
confidence: 99%
“…28 For nocturia, there seems to be no difference between vaginal delivery and CS. 21,28 Most recently a study by Blomquist et al (2018) 29 reported that CS was associated with a significantly lower risk for SUI, OAB, and pelvic organ prolapse (POP) compared with vaginal delivery, while operative vaginal delivery was associated with significantly greater risk of anal incontinence and POP.…”
Section: Mode Of Delivery and The Role Of Cesarean Section In The Dmentioning
confidence: 99%